Women’s mood at high altitude. sexual dimorphism in hypoxic stress modulation by the tryptophan–melatonin axis - Alcantara-Zapata, D. E.; Lucero, N.; De Gregorio, N.; Astudillo Cornejo, P.; Ibarra Villanueva, C.; Baltodano-Calle, M. J.; Gonzales, G. F.; Behn, C. (Frontiers in Physiology, 2023)
Sexual (and gender)-dimorphism in tolerance to hypobaric hypoxia increasingly matters for a differential surveillance of human activities at high altitude (HA). At low altitudes, the prevalence of anxiety and depression in women has already been found to double when compared with men; it could be expected to even increase on exposure to HA. In purposefully caring for the health of women at HA, the present work explores the potential involvement of the tryptophan (Trp)–melatonin axis in mood changes on exposure to hypobaric hypoxia. The present work highlights some already known anxiogenic effects of HA exposure. Hypoxia and insomnia reduce serotonin (5-HT) availability; the latter defect being expressed as failure of brown adipose tissue (BAT) activation and mood disorders. Rapid eye movement (REM) sleep organization and synapsis restoration that are additionally affected by hypoxia impair memory consolidation. Affective complaints may thus surge, evolving into anxiety and depression. Sex-related differences in neural network organization and hormonal changes during the menstrual cycle, and certainly also during the life cycle, underscore the possibility of 5-HT–related mood alterations, particularly in women on HA exposure. The mean brain rate of 5-HT synthesis at sea level is already 1.5-fold higher in males than in females. sexual dimorphism also evidences the overexpression effects of SERT, a 5-HT transporter protein. Gonadal and thyroid hormones, as influenced by HA exposure, further modulate 5-HT availability and its effects in women. Besides caring for adequate oxygenation and maintenance of one’s body core temperature, special precautions concerning women sojourning at HA should include close observations of hormonal cycles and, perhaps, also trials with targeted antidepressants.